"Do it cheaper": A cost‐effective Endobag for small specimens. Issue 9 (30th August 2021) - Chatzipapas, Ioannis; Kathopoulis, Nikolaos; Samartzis, Konstantinos; Kypriotis, Konstantinos; Siemou, Panagiota; Protopapas, Athanasios
Abstract: A simple technique that permits to reduce the cost during gynecologic laparoscopic surgery. Small specimens may be retrieved with the use of a modified urine pediatric bag. Abstract : A simple technique that permits to reduce the cost during gynecologic laparoscopic surgery. Small specimens may be retrieved with the use of a modified urine pediatric bag.